A method of introducing alloying elements into a ferritic stainless steel weld

CN120480477BActive Publication Date: 2026-10-30SHANXI TAIGANG STAINLESS STEEL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510938811.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-08
Publication Date
2026-10-30
Estimated Expiration
2045-07-08

AI Technical Summary

Technical Problem

[0003]然而,现有文献及技术资料表明,关于不锈钢活性焊剂的研究一般都围绕奥氏体类不锈钢,而关于铁素体类不锈钢的研究内容和结果很少,因此,研究向铁素体不锈钢焊缝过渡合金元素的方法对于铁素体不锈钢的推广应用具有重要的意义

Benefits of technology

本发明的向铁素体不锈钢焊缝中过渡合金元素的方法起到了改善组织及提升力学性能的作用,满足了使用要求,提升了焊缝的性能;本发明实施例根据所需过渡的合金元素来选取相应的活性焊剂,提高了元素的过渡效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120480477B_ABST
    Figure CN120480477B_ABST
Patent Text Reader

Abstract

The present application relates to a method for transition of alloying elements into ferritic stainless steel welds, comprising: obtaining a mixture of active flux and powder of metal elements to be transitioned; coating the mixture on the area to be welded with a binder capable of complete volatilization; and welding after the binder is completely volatilized. The method improves the structure and mechanical properties, meets the use requirements, and improves the performance of the weld; and the corresponding active flux is selected according to the alloying elements to be transitioned, thereby improving the transition efficiency of the elements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of welding technology, and specifically relates to a method for transferring alloying elements into ferritic stainless steel welds. Background Technology

[0002] Activating flux TIG welding (A-TIG) is a TIG welding method that involves applying a thin layer of active flux (mainly oxides and fluorides) to the surface of the workpiece. This welding method not only significantly increases the penetration depth but also improves the microstructure and properties of the weld. Especially for ferritic stainless steels with poor weldability, it can increase the weld's aspect ratio, refine the grain size, and, by adding beneficial alloying elements such as titanium, aluminum, and nickel powder to the active flux, transfer these beneficial alloys into the weld, compensating for the low alloy content and poor weldability of ferritic stainless steel. Studies have shown that adding appropriate amounts of these elements to ferritic stainless steel welds can refine the grain size and improve the weld's mechanical properties and corrosion resistance.

[0003] However, existing literature and technical data indicate that research on active fluxes for stainless steel generally focuses on austenitic stainless steels, while research on ferritic stainless steels is scarce. Therefore, researching methods for transitioning alloying elements to ferritic stainless steel welds is of great significance for the promotion and application of ferritic stainless steels. Summary of the Invention

[0004] In order to solve all or part of the above problems, the present invention aims to provide a method for transferring alloying elements into ferritic stainless steel welds.

[0005] According to one aspect of the present invention, a method for transferring alloying elements into a ferritic stainless steel weld is provided, comprising: A mixture of active flux and powder of the metal element to be transitioned was obtained; The mixture is applied to the area to be soldered using a fully volatile adhesive; and Welding is performed after the adhesive has completely evaporated.

[0006] Furthermore, if the powder of the transition metal element is aluminum powder, the active flux, by mass percentage, includes the following components: 80%~90% of a mixture of MgO powder and TiO2 powder, and 10%~20% of SiO2 powder.

[0007] Furthermore, aluminum powder accounts for 25% to 50% of the total mass of the active flux.

[0008] Furthermore, if the powder of the transition metal element is titanium powder, the active flux, by mass percentage, includes the following components: 35%~45% CaF2 powder, 35%~45% NaF powder, and 10%~20% SiO2 powder.

[0009] Furthermore, titanium powder accounts for 20% to 30% of the total mass of the active flux.

[0010] Furthermore, if the powder of the transition metal element is nickel powder, the active flux, by mass percentage, includes the following components: 20%~25% TiO2 powder, 20%~25% SiO2 powder, 20%~25% CaF2 powder, and 20%~25% NaF powder.

[0011] Furthermore, nickel powder accounts for 20% to 40% of the total mass of the active flux.

[0012] Furthermore, the completely volatile adhesive is industrial alcohol; The step of applying the mixture to the area to be welded using a completely volatile adhesive specifically involves using industrial alcohol as an adhesive to apply the mixture to the area to be welded, with a coating thickness of 0.1~0.3mm.

[0013] Furthermore, the step of welding after the adhesive has completely evaporated specifically means: TIG welding is performed after the adhesive has completely evaporated.

[0014] Furthermore, after welding is performed after the adhesive has completely evaporated, the method further includes cleaning the welded area after welding.

[0015] As can be seen from the above technical solution, the method for transferring alloying elements into ferritic stainless steel welds provided by the present invention has the following beneficial effects: The method for transferring alloying elements into ferritic stainless steel welds according to the present invention improves the microstructure and enhances the mechanical properties, meets the application requirements, and improves the performance of the weld. The embodiments of the present invention select the appropriate active flux according to the alloying elements to be transferred, thereby improving the transfer efficiency of the elements. Attached Figure Description

[0016] Figure 1 A schematic diagram illustrating the mechanism by which the activator increases its melting depth; Figure 2 This is a flowchart of a method for transferring alloying elements into ferritic stainless steel welds according to an embodiment of the present invention. Detailed Implementation

[0017] To better understand the purpose, structure, and function of this invention, the following detailed description, in conjunction with the accompanying drawings, provides a method for transferring alloying elements into ferritic stainless steel welds according to this invention.

[0018] This invention relates to a method for transferring alloying elements into ferritic stainless steel welds, including the formulation of active fluxes corresponding to the addition of aluminum, titanium, and nickel elements to the ferritic stainless steel weld, i.e., different active fluxes are formulated for different metal elements to be transferred; this invention is proposed based on research and summarization of the transition characteristics of different active elements to different alloying elements, while taking into account feasibility and economy, and clarifies the effectiveness of different active fluxes in the transition of the above-mentioned metal elements.

[0019] In ferritic stainless steel welds, some metallic elements such as aluminum, titanium, and nickel combine with interstitial elements like C, N, and O to form interstitial phases such as oxides or carbonitrides, which are dispersed throughout the ferrite matrix as second-phase particles. These metallic elements not only strengthen the base metal, but their atomic presence also enhances the material's corrosion resistance. More importantly, these high-temperature stable second-phase particles can, to some extent, prevent excessive grain growth during welding thermal cycling, thus reducing the tendency for weld performance to deteriorate.

[0020] However, except for nickel, all of these elements are prone to oxidation and burn-off at the high welding temperatures. Therefore, the content of microalloying elements in the weld is lower than that in the base metal, making grain coarsening and performance deterioration in the weld inevitable. However, adding excessive trace elements to the ferritic stainless steel base metal is neither economical nor necessary; local alloying of the weld metal is the most ideal solution.

[0021] The main role of active flux in the welding process is to increase the weld penetration (depth-to-width ratio) under the same current conditions. The mechanism is mainly based on the following theories. Currently, it is generally believed that the increase in penetration is the result of the combined effect of multiple factors.

[0022] 1. Anode spot shrinkage theory: Adding sulfides, chlorides, or oxides to the molten pool significantly reduces the size of the anode spots and increases the weld penetration. The theory suggests that adding high-melting-point activators suppresses the amount of metal vapor generated on the molten pool surface. With less metal vapor, only a small area of ​​metal near the anode spots is vaporized and ionized, constricting the arc's conductive path, increasing arc pressure, and accelerating, expanding, and deepening the flow of molten metal within the pool, thus increasing the weld penetration.

[0023] The active flux widens the current lines of the molten metal in the weld pool, creating a Lorenz force. Due to the change in the cross-section of the conductor, an axial component pointing towards the larger cross-section is generated, the magnitude of which can be determined by equation (1): (1) In the formula, p is the Lorenz force in N; I is the welding current in A; R1 and R2 are the radii of the cross-section of the fluid-carrying body in mm; and μ is the permeability at a constant volume. As can be seen from equation (1), the magnitude of the electromagnetic force depends on the magnitude of the welding current and the degree of current line widening. In active flux welding, the radius of the polar spot is much smaller than that in ordinary welding, and the axial electromagnetic component P increases. It is this force that causes the molten metal in the molten pool to flow directionally from the surface of the molten pool to the bottom of the molten pool. Under the action of this high-temperature molten metal flow, the weld penetration depth increases.

[0024] 2. Theory of surface tension gradient change: Within a molten pool, three forces exist: electromagnetic force, buoyancy, and surface tension. The flow field generated by the electromagnetic force conducts heat from the arc center to the bottom of the pool, forming a deep molten pool. Buoyancy and a negative surface tension gradient cause the molten pool to flow upwards, forming a shallow and wide weld. The effect of buoyancy is minimal. The simultaneous action of these three forces results in two circulation modes within the molten pool: one at the surface, determined by surface tension; and another within the pool, determined by the electromagnetic force. The rates of these two circulations differ, with the second circulation being much slower than the first. Therefore, heat conduction from the heat source to the root of the molten pool is interrupted by the first circulation, resulting in a shallow and wide weld. However, when surface-active elements are present on the molten pool surface, the surface tension gradient becomes positive, altering the direction of the first circulation. The increased flow of the molten pool enhances heat conduction, forming a deep and narrow weld, such as... Figure 1 As shown.

[0025] 3. Arc contraction theory: The components of active flux are all polyatomic molecules, so they undergo thermal dissociation in an arc atmosphere. Since thermal dissociation is an endothermic reaction, the arc contracts according to the principle of minimum voltage.

[0026] Based on the above principles and the influence of active flux on the arc and molten pool, alloying the weld metal by adding microalloying elements to the active flux is a feasible and relatively ideal alloying transition method. However, the transition effects of different active fluxes or combinations of active fluxes on different alloying elements need further research so that different proportions of active flux can be used according to the alloying elements to be transitioned.

[0027] It needs to be further clarified that although active fluxes such as TiO2 and Al2O3 contain titanium and aluminum, these oxides have very high melting points (1840℃ and 2054℃, respectively) and high-temperature stability. Although tests show that the amount of titanium and aluminum in the weld metal obtained by using fluxes containing the above substances increases, most of it exists in the form of oxides rather than carbonitrides or atomic forms that can prevent grain coarsening. Therefore, the effect of active flux alone on refining weld performance and improving performance is limited. Transmitting alloying elements into the weld through active flux is an ideal solution.

[0028] Although active fluxes without added alloy powder can refine the grain size of stainless steel weld metal, the initial purpose of researching active fluxes was to improve the aspect ratio of austenitic stainless steel welds. For ferritic stainless steels, introducing appropriate amounts of microalloying elements into the weld, depending on specific requirements, can further improve the microstructure and enhance properties.

[0029] This invention is based on research on the influence of microalloying elements in ferritic stainless steel on the microstructure and properties of welded joints and the application of active flux in stainless steel welding. The aim is to obtain an effective and economical method for transferring alloying elements into ferritic stainless steel welds, and to summarize the corresponding relationships between the transfer capabilities of different active fluxes for various alloying elements, so as to achieve the effectiveness and economy of active fluxes. The invention also aims to select appropriate active flux formulations based on the alloying elements to be transferred, thereby improving the transfer efficiency of metal elements.

[0030] Specifically, such as Figure 2 As shown in the figure, a method for transferring alloying elements into ferritic stainless steel welds according to an embodiment of the present invention includes the following steps: Step S001: Obtain a mixture of active flux and powder of the metal element to be transitioned; Step S002: Apply the mixture to the area to be soldered using a fully volatile adhesive; and Step S003: Welding is performed after the adhesive has completely evaporated.

[0031] Ferritic stainless steel is generally used in thin sheet form (thickness ≤ 3mm), and TIG welding is the most common method. Therefore, achieving weld metal alloying through A-TIG welding is scientifically sound and feasible. Beneficial alloying elements in ferritic stainless steel include aluminum, titanium, and nickel. These elements typically comprise less than 0.3% of the stainless steel, but play a crucial role in improving its mechanical properties, corrosion resistance, and weldability. These trace elements can exist in stainless steel as one or more combinations, improving microstructure and enhancing mechanical properties in different applications. Therefore, in certain specific applications, technicians may wish to introduce specific alloying elements into the weld metal during the welding process to meet usage requirements and further improve weld performance. To determine the transition efficiency of different substances for each element, the following experiments were designed to summarize the relationship between active substances and transition elements.

[0032] Typical active materials selected for the experiment included oxides SiO2, TiO2, and MgO, and fluorides CaF2 and NaF. The selected stainless steel material was medium-chromium ultra-pure ferritic stainless steel SUS441 (022Cr18NbTi). Medium-chromium ultra-pure ferritic stainless steel is a typical niobium-titanium bistable single-phase ferritic stainless steel. The thickness of the stainless steel plate used in the experiment was 3 mm. The tungsten inert gas (TIG) welding method of bead-on-plate welding was adopted, with DC positive polarity, welding current of 120~150A, welding speed of 300 mm / min, and heat input range of 0.25~0.3 KJ / mm. Combinations of activator and metal powder as shown in Table 1 were selected for the experiment. The mass of metal powder was 10-30% of the corresponding activator. After completion, samples were taken and optical microscope specimens were prepared to observe the metallographic structure for qualitative study of weld grain size. The results were compared with the specimens without flux. If the grain size changed significantly, it was considered that the element had effectively transitioned into the weld metal.

[0033] Table 1: Different combinations of surfactants and metal powders and their corresponding results

[0034] Table 1 shows that different active materials exhibit significantly different transition characteristics for each alloying element. It can be concluded that oxides have a better transition effect on aluminum; fluorides have a better transition effect on titanium; and both oxides and fluorides are suitable for the transition of nickel. To achieve effective transition, active materials with good transition properties should be selected, rather than those with poor transition properties. While SiO2 is the most significant active material for increasing weld penetration, excessive amounts can lead to increased Si content in the weld, resulting in deteriorated performance; therefore, its content should not be excessive (≤25%).

[0035] In summary, regarding the mixture of active flux and powder of the transition metal element obtained in S001: the active flux selected varies depending on the transition metal element. The following discussion focuses on aluminum powder, titanium powder, and nickel powder as the transition metal element powders: If the transition metal powder is aluminum powder, the active flux, by mass percentage, comprises the following components: 80%–90% of a mixture of MgO powder and TiO2 powder, and 10%–20% of SiO2 powder. Aluminum powder accounts for 25%–50% of the total mass of the active flux.

[0036] If the transition metal powder is titanium powder, the active flux, by mass percentage, includes the following components: 35%~45% CaF2 powder, 35%~45% NaF powder, and 10%~20% SiO2 powder. Among them, titanium powder accounts for 20%~30% of the total mass of the active flux.

[0037] If the transition metal powder is nickel powder, the active flux, by mass percentage, comprises the following components: 20%–25% TiO2 powder, 20%–25% SiO2 powder, 20%–25% CaF2 powder, and 20%–25% NaF powder. Nickel powder accounts for 20%–40% of the total mass of the active flux.

[0038] For S002, the mixture is applied to the area to be soldered using a completely volatile adhesive: the completely volatile adhesive is industrial alcohol; the specific method of applying the mixture to the area to be soldered using a completely volatile adhesive is: using industrial alcohol as an adhesive to apply the mixture to the area to be soldered, with a coating thickness of 0.1~0.3mm.

[0039] S003 Welding is performed after the adhesive has completely evaporated. Specifically, TIG welding is performed after the adhesive has completely evaporated.

[0040] After welding is performed after the S003 adhesive has completely evaporated, the method of this embodiment of the invention further includes cleaning the welded area after welding.

[0041] The following examples verify the method of the embodiments of the present invention to confirm the effectiveness of the active flux formulation design in the embodiments of the present invention.

[0042] The stainless steel used in the experiment was still 3mm thick SUS441 (022Cr18NbTi) ferritic stainless steel. The purpose of the experiment was to introduce an appropriate amount of aluminum into the weld to refine the grain and improve mechanical properties. Relevant literature indicates that an aluminum content of around 0.3% in stainless steel has the best effect on improving the microstructure and properties of the weld. In this experiment, the aluminum content was significantly increased to enhance the comparative effect. To further verify the above conclusions on the effect of aluminum on different active materials, the following experiment was designed: Seven oxides and fluorides were selected and mixed with aluminum powder in a 1:1 ratio. After being mixed evenly with alcohol, the mixture was applied to the area to be welded on the stainless steel plate. Welding was carried out after the alcohol had completely evaporated. The polarity was DC positive, the welding current was 120~150A, the welding speed was 300mm / min, and the heat input range was 0.25~0.3KJ / mm. The seven oxides and fluorides were SiO2, TiO2, Cr2O3, MgO, NaF, CaF2, and ZnF. Al2O3 without added aluminum powder was also selected. Experiments were conducted individually with these eight substances to investigate whether they could function as alloying agents. Elemental analysis of the weld metal after surface slag removal was performed using an electric spark spectrometer. The results showed that MgO had the most significant transition effect on aluminum, with the highest aluminum content in the weld reaching 1.5%. TiO2 also had a strong transition effect on aluminum, with aluminum content ranging from 0.75% to 0.85%. The aluminum content of the Cr2O3 sample was 0.7%. Fluorides had relatively low transition effects on aluminum, with aluminum content ranging from 0.14% to 0.4% in the weld. The aluminum content of the single-component Al2O3 sample was 0.015%, essentially equivalent to that in the base metal, indicating no aluminum transition to the weld. Furthermore, while aluminum was transitioned to the weld through SiO2 and TiO2, the Si and Ti content in the weld also increased (Si increased from 0.35% to 1.05%; Ti increased from 0.13% to 0.61%). Excessive Si in ferritic stainless steel increases brittleness; therefore, the SiO2 content in active fluxes for ferritic stainless steel should be controlled.

[0043] It should be noted that, unless otherwise stated, the technical or scientific terms used in this application should have the ordinary meaning as understood by one of ordinary skill in the art to which this invention pertains.

[0044] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. These modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be covered within the scope of the claims and specification of the present invention. In particular, as long as there is no structural conflict, the various technical features mentioned in the embodiments can be combined in any way. The present invention is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.

Claims

1. A method for transferring alloying elements into ferritic stainless steel welds, characterized in that, include: A mixture of active flux and powder of the metal element to be transitioned was obtained; The mixture is applied to the area to be soldered using a fully volatile adhesive; as well as Welding should be performed after the adhesive has completely evaporated; If the transition metal powder is aluminum powder, then the active flux, by mass percentage, comprises the following components: 80%~90% of a mixture of MgO powder and TiO2 powder, 10%~20% of SiO2 powder, and aluminum powder accounting for 25%~50% of the total mass of the active flux; If the transition metal element powder is titanium powder, then the active flux, by mass percentage, comprises the following components: 35%~45% CaF2 powder, 35%~45% NaF powder, 10%~20% SiO2 powder, and titanium powder accounts for 20%~30% of the total mass of the active flux; If the transition metal element powder is nickel powder, then the active flux, by mass percentage, includes the following components: 20%~25% TiO2 powder, 20%~25% SiO2 powder, 20%~25% CaF2 powder, and 20%~25% NaF powder, with nickel powder accounting for 20%~40% of the total mass of the active flux.

2. The method for transferring alloying elements into ferritic stainless steel welds according to claim 1, characterized in that, The completely volatile adhesive is industrial alcohol; The step of applying the mixture to the area to be welded using a completely volatile adhesive specifically involves using industrial alcohol as an adhesive to apply the mixture to the area to be welded, with a coating thickness of 0.1~0.3mm.

3. The method for transferring alloying elements into ferritic stainless steel welds according to claim 1, characterized in that, Specifically, welding is performed after the adhesive has completely evaporated.

4. The method for transferring alloying elements into ferritic stainless steel welds according to claim 1, characterized in that, After welding is performed after the adhesive has completely evaporated, the method further includes cleaning the welded area post-weld.

Citation Information

Patent Citations

  • Active solder for welding ferritic stainless steel with fined grains and preparation method of active solder

    CN103418938A